Efeitos da luz pulsada no metabolismo e nas características físico-químicas de frutos de manga “Tommy Atkins” durante o armazenamento - Lopes, Mônica Maria de Almeida (2015)
The pulsed light (PL) is a technology emergent used as abiotic stressor to increase the content of phytochemicals of fruits and vegetables. However, their effects vary depending on the cultivar, the dose hormetic, the mode of application of dose and the maturation stage of fruits. In this work, we start from the main hypothesis that changes in the metabolism of the fruits of mangoes treated with low doses of pulsed light would trigger responses that result in a positive impact on the content of phytochemicals, without any negative effect on the fruit quality parameters. This work was divided into three chapters. Chapter I is a literature review and state of the art of the main topics covered throughout the study. In the second chapter (experiment I), mangoes mature physiologically (maturation stage 3) were subjected to a hormetic dose of pulsed light 0.6 J cm-2 and analyzed after 7 days storage at 20 °C, for the physicochemical characteristics [soluble solid (SS), titratable acidity (TA), SS/TA ratio, overall appearance, color and firmness], enzymatic antioxidant metabolism [superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX)] and non-enzymatic [ascorbate, total carotenoids, total anthocyanins, yellow flavonoids, total phenolic, mangiferin content and total antioxidant activity], membrane integrity [lipid peroxidation (MDA), hydrogen peroxide content and electrolyte leakage], phenylalanine ammonia lyase activity (PAL), enzymes of enzymatic browning [polyphenoloxidase (PPO), peroxidase of guaiacol (GPOD) and activity of enzymes wall cell [pectinmethylesterase (PME) and polygalacturonase (PG)] and the influence of treatment on tissue histology. The activity of antioxidant enzymes such as catalase and superoxide dismutase was found to be substantially enhanced in both the epicarp and the mesocarp of fruits exposed to PL after 7 days at 20 ºC. There were no differences in indicators of cell wall and membrane integrity such as MDA content suggesting that the PL-associated oxidative stress was effectively prevented by the enhanced activity of antioxidant enzymes after 7 days. Activities of cell wall enzymes were reduced after 7 days in the PL-treated fruits. Microscopic as well as macroscopic observations confirmed that PL-treated fruits were not damaged. We observed that contents in total carotenoids, in total phenolic, and, to a lesser extent, in vitamin C, were dramatically increased after 7 days, generally in both the epicarp and the mesocarp PL-treated resulting in fruits with high antioxidant capacity. Carotenoids increased 350% in treated-pulp at J7. The higher levels in phenolics in treated-peel (+97%) were associated with enhanced activity of PAL (+98%) and enhanced content in mangiferin (+42%). Although G-POD in the mesocarp and PPO in the epicarp increased 1268% and 22% respectively, after 7 days in the PL-treated fruits, we did not observe increases in browning. Was observed at the end of the experiment I an increase of phytochemicals in mangoes subjected to hormetic dose of 0.6 J cm-2 without negative changes in fruit quality. In the third chapter (experiment II), mangoes minimally processed (maturation stage 4) were subjected to four different treatments: control (not flashed), 1 pulse, 4 pulses, and 1 pulse (4 days) prior to storage at 6 ºC in order to assess whether the mode of application of the different doses used could interfere on physiochemical variables [firmness, color, SS, loss weight and rate respiration] the bioactive compounds [ascorbate (AsA) and carotenoids] and total antioxidant activity by a storage period of 7 days at 6 ºC. Samples flashed with 1 pulse during 4 alternated days (4 x 0.6 J cm-2 = 2.80 J cm-2) increased the total ascorbate (AsA) (~40% more than the control) at time 7 days but the cubes of mangoes are darker than treatment that received the same dose of 4 successive pulses (2.80 J cm-2). At end of storage fresh cut mangoes received 4 successive pulses exhibited a better quality in comparison to the other treatments that was associated a higher content carotenoid (0.894 mg g-1) and antioxidant activity (~145 μmol trolox 100 g-1). In conclusion, our data suggest that a hormetic dose of pulsed light can be used to increase concentrations of phytochemical compounds without negative effects on the quality criteria.